Esclavos del destino: elegidos y marginados en los rituales religiosos Geto-Dacios, a propósito de un pasaje de Herodoto (HDT. IV, 94) - Carbó García, Juan Ramón (ARYS. Antigüedad: Religiones y Sociedades, 2020)
From an account in the historic work of Herodotus (Book IV, 94), which is about the religious believings of the Getae and about their religious rituals, it´s intended to analyze an alleged show of oppression and social and religious exclusion. This could happen like a result of a mistake in one of those rituals, in which the Getae “sent” a chosen messenger to their main deity, Zalmoxis by drawing lots, to make him know about the problems, requests and gratitudes of his people´s different members. All this ritual is not but a show of submission and inwardness of the dependence.